2016
DOI: 10.1097/brs.0000000000001464
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Hemangiomas and Their Correlation With Other Pathologies

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…Localized trauma in humans has been associated with subsequent development of hemangiomas at various sites but is generally found to be subcutaneous or close to underlying bony structures. [24][25][26][27] Given the association between localized trauma and development of hemangiomas in humans, the same could be a potential concern in nonhuman primates. A positive correlation between increasing age and increasing neoplasia incidence in multiple species of primates including humans and macaques exists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Localized trauma in humans has been associated with subsequent development of hemangiomas at various sites but is generally found to be subcutaneous or close to underlying bony structures. [24][25][26][27] Given the association between localized trauma and development of hemangiomas in humans, the same could be a potential concern in nonhuman primates. A positive correlation between increasing age and increasing neoplasia incidence in multiple species of primates including humans and macaques exists.…”
Section: Discussionmentioning
confidence: 99%
“…It is unusual that the hemangiomas in this animal occurred at this specific anatomic location. Localized trauma in humans has been associated with subsequent development of hemangiomas at various sites but is generally found to be subcutaneous or close to underlying bony structures . Given the association between localized trauma and development of hemangiomas in humans, the same could be a potential concern in nonhuman primates.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of reports of CCM is to some degree limited by the fact that, as radiologists and spinal clinicians are aware, intraosseous vascular malformations are common findings at routine CT and MRI of adults. An autopsy study [5] showed that intraosseous vascular malformations were present in 11% of bodies examined, and later CT and MRI studies of large numbers of adults showed the malformations present in approximately 26% of subjects [10,11]. Intraosseous vascular malformations are known to have an increasing prevalence with age [10].…”
mentioning
confidence: 99%
“…An autopsy study [5] showed that intraosseous vascular malformations were present in 11% of bodies examined, and later CT and MRI studies of large numbers of adults showed the malformations present in approximately 26% of subjects [10,11]. Intraosseous vascular malformations are known to have an increasing prevalence with age [10]. Most are clinically unimportant, although unusually large or fat-poor malformations are at greater risk of pathologic fracture [12][13][14].…”
mentioning
confidence: 99%
“…Другие авторы [7], основываясь на результатах обследования 196 больных, пришли к выводу, что основной причиной развития ГП является нарушение микроциркуляции (с повреждением эндотелия микрососудов) внутри тела позвонка, приводящее в конечном итоге к гиперваскуляризации. ГП у наблюдаемых больных были связаны с поражениями дисков (р=0,004), травмами позвоночника в анамнезе (р=0,037), злокачественными новообразованиями (р=0,016), сахарным диабетом (р=0,023), сердечно-сосудистыми заболеваниями (р=0,003), но не с ожирением.…”
unclassified